Factores determinantes asociados al síndrome de burnout en los profesionales de enfermería del Hospital Provincial Martín Icaza Babahoyo, diciembre 2022 - mayo 2023. - Izquierdo Trejo, Joselyn Esther (2023)
A study was conducted on the determinant factors associated with Burnout Syndrome in nursing professionals of the Hospital Provincial Martín Icaza -Babahoyo. To determine the incidence of Burnout Syndrome, a mixed research methodology was established, that is, the use of qualitative and quantitative methods that allow relating the results and thus deepen the current state of the phenomenon to be investigated. Two instruments were used to measure the presence of Burnout Syndrome in the sample. As for the quantitative data, the Maslach Burnout Inventory (MBI) by Cristina Maslach, developed in 1981, was chosen. The Spanish version was made by Nicolás Seisdedos in 1997. The questionnaire is made up of 22 questions that express the feelings and thoughts of the population studied. The scale evaluated Burnout factors through three subscales: emotional exhaustion, depersonalization, and job fulfillment. The analysis was descriptive, and explanatory based on a field design. For the qualitative data, a 36-item semi-structured interview was elaborated and applied to a sample of 12 leading nursing professionals from each service. The data were transcribed and presented in the form of tabulations and reports. The results showed that 55% of this population suffers from Burnout Syndrome with the presence of some symptoms of emotional exhaustion. The 38% suffer from depersonalization and 7% from low personal fulfillment of the nursing professionals who work at the Hospital Provincial Martín Icaza Babahoyo.